Marketing Strategy of Inpari 40 and Kusuma 06 Rice Farming (Oryza sativa L.) in Mangulewa Village, Ngada Regency - Rofinus Neto Wuli; Marten Umbu Kaleka; Kornelia Roswita Moi (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The rice sector is strategic for food security and rural welfare in Indonesia. In Ngada Regency, dry unhusked rice (GKG) production declined from 57,618.67 tons in 2023 to 46,144.71 tons in 2024, while farm-gate prices remained volatile. Studies on the marketing of specific superior varieties such as Inpari 40 and Kusuma 06 at the village level remain scarce. Objective: This study analyzes the marketing strategy of Inpari 40 and Kusuma 06 rice farming (Oryza sativa L.) in Mangulewa Village, Ngada Regency, focusing on marketing channels, marketing margins, and farmers' share. Methods: A convergent mixed-methods design was applied between February and May 2025. Thirty respondents (25 purposively selected farmers and 5 traders) were interviewed, and data were triangulated with observation and documentation. Qualitative data were analyzed using the Miles-Huberman model, while quantitative data employed marketing-margin and farmers'-share formulas. Results: Findings indicate a direct (zero-level) channel for Inpari 40 organic rice and Kusuma 06 seed, with a farmers' share of 100% for direct sales and an average marketing margin of IDR 3,500/kg when traders are involved. Inpari 40 is sold as organic rice at IDR 15,000/kg, and Kusuma 06 as unlabeled seed at IDR 20,000/kg. Digital promotion via WhatsApp and Facebook contributed approximately 30% of orders. Conclusion: An integrated strategy combining product differentiation, direct channels, and digital promotion enhances farmers' share and supports farming sustainability. Future research should test these findings on a larger sample and include cost-benefit analyses.